Investigation of the Synthesis of Benzofuroindolines from N-Hydroxyindoles: An O-Arylation/[3,3]-Sigmatropic Rearrangement Sequence - Tomakinian, Terry; Kouklovsky, Cyrille; Vincent, Guillaume (Synlett, 2015)
We report the demonstration that sensitive N-hydroxyindoles can be O-arylated under transition-metal-free conditions with biaryliodonium salts. The subsequent spontaneous [3,3]-sigmatropic rearrangement delivers benzofuroindolines derived from tryptamine. We also describe the practical synthesis of N-hydroxyindoles by oxidation of indolines with m-CPBA.
Keywords: N-hydroxyindoles; diazonamide A; azonazine; benzofuroindoline; [3,3]-sigmatropic rearrangement